2010
DOI: 10.1002/jsfa.4109
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical characterization of a bacteriocin‐like inhibitory substance produced by Enterococcus faecium MXVK29, isolated from Mexican traditional sausage

Abstract: Biochemical characteristics of BLIS produced by E. faecium MXVK29 suggested that it belongs to Class IIa of the Klaenhammer classification and could be considered as a natural food preservative, although further studies need to be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 51 publications
(54 reference statements)
0
8
0
1
Order By: Relevance
“…Bacteriocins are ribosomal antimicrobial peptides active against closely related and non-related sensitive bacterial strains by forming pores in the cytoplasmic membrane and responsible for the reduction of microbial LAB competitors under stress conditions. Several studies have demonstrated the potential of bacteriocins to be applied for food preservation and in the pharmaceutical industry for their action against spoilage microorganisms and pathogens such Listeria monocytogenes and Staphylococcus aureus [16][17][18].…”
Section: Lactic Acid Bacteriamentioning
confidence: 99%
“…Bacteriocins are ribosomal antimicrobial peptides active against closely related and non-related sensitive bacterial strains by forming pores in the cytoplasmic membrane and responsible for the reduction of microbial LAB competitors under stress conditions. Several studies have demonstrated the potential of bacteriocins to be applied for food preservation and in the pharmaceutical industry for their action against spoilage microorganisms and pathogens such Listeria monocytogenes and Staphylococcus aureus [16][17][18].…”
Section: Lactic Acid Bacteriamentioning
confidence: 99%
“…This is in accordance with the observation that the sensitivity of Listeria to AMPs depends on the species considered. However, since it also depends on the strain for each species (Alvarez-Cisneros et al 2010), and namely on its serotype for L. monocytogenes strains (Mukherjee et al 2011), the anti-listerial activity of Asiago cheese WSEs should be assayed with a larger panel of L. innocua and L. monocytogenes strains including other serotypes than the serotype of L. monocytogenes strain 162 (serotype 1/2a), before it could be proposed that L. innocua is more sensitive to Asiago cheese WSEs than L. monocytogenes.…”
Section: Anti-listerial Activity Of Asiago Cheese Water-soluble Extractsmentioning
confidence: 99%
“…According to Álvarez‐Cisneros et al . (), Enterococcus faecium MXVK29 produced a bacteriocin‐like inhibitory substance (BLIS) with anti‐ Listeria activity , thermotolerance and with a low molecular weight (3·5 kDa), which could be used as a natural preservative. Therefore, the purpose of this study was to analyse the safety determinants of E. faecium MXVK29.…”
Section: Introductionmentioning
confidence: 99%
“…However, the selection of enterococci for food processing applications is a difficult task due to the potential risks to human health (De Vuyst et al 2003;Ben Omar et al 2004). According to Alvarez-Cisneros et al (2010), Enterococcus faecium MXVK29 produced a bacteriocin-like inhibitory substance (BLIS) with anti-Listeria activity, thermotolerance and with a low molecular weight (3Á5 kDa), which could be used as a natural preservative. Therefore, the purpose of this study was to analyse the safety determinants of E. faecium MXVK29.…”
Section: Introductionmentioning
confidence: 99%